Measuring the Impact of APOS Theory-Based Contextual Mathematics Assignments on the Mathematical Communication Skills of Prospective Teacher Students - Jaya, Ilham; Nurkhasyanah, Alfiyanti; Fitria, Anna; Salsabila, Ismi (Universitas Muhammadiyah Mataram, 2026)
Mathematical communication skills are essential for conveying ideas, interpreting symbols, and linking abstract concepts to contextual phenomena. This study aims to measure the effectiveness of applying APOS theory-based contextual tasks in improving the mathematical communication skills of prospective teacher students. This study uses a quasi-experimental design with a non-equivalent control group model, involving an experimental class that receives contextual task-based learning using the APOS theory approach and a control class that follows conventional learning. The instrument used was a mathematical communication skills test covering five main indicators, namely the ability to express ideas in writing, use representations, explain procedures, relate concepts to real contexts, and construct mathematical arguments. The data were analyzed using the Rasch model, normality test, homogeneity test, independent t-test, score improvement analysis, and PLS-SEM-based structural modeling. The results indicate that the instrument demonstrates strong validity and reliability, as reflected by average Infit and Outfit MNSQ values of 1.00, item reliability of 0.89, and person reliability of 0.84. Significant differences were found between the experimental and control groups across all indicators of mathematical communication skills, with higher posttest mean scores in the experimental group (76.10) compared to the control group (49.87), as well as greater learning gains in the experimental group (N-Gain 68.27%) than in the control group (33.18%). The structural model further confirms the positive contribution of APOS theory to mathematical communication skills, particularly in explaining procedures (β = 0.323) and using mathematical representations (β = 0.257). Overall, this study confirms that the application of APOS theory-based contextual tasks is effective in strengthening the mathematical communication skills of prospective teachers and provides important implications for the development of a more contextual and meaningful mathematics education curriculum.